2002
DOI: 10.1152/jn.2002.88.2.639
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Junction Channels Between Rat Glomus Cells During Normoxia and Hypoxia

Abstract: The activity of gap junction channels between cultured and clustered carotid body glomus cells of the rat was studied with dual voltage clamping during normoxia (PO(2) 300 Torr) and hypoxia induced by sodium dithionite (Na(2)S(2)O(4)) or 100% N(2). Na(2)S(2)O(4) reduced the saline PO(2) to approximately 10 Torr, whereas 100% N(2) reduced ambient O(2) to approximately 60 Torr. The following observations were made. 1) In normoxia, the intercellular macroconductance (G(j) = 3.0 +/- 1.01 ns, mean +/- SE) was chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Presence of spontaneous oscillation in [Ca 2+ ] i has also been reported earlier [28]. Because glomus cells in the carotid body are believed to be electrically-coupled by gap junctions [2], it is possible that spontaneous [Ca 2+ ] i oscillations occur under normoxic conditions for all glomus cells in vivo, but not in dispersed cells. Such [Ca 2+ ] i oscillations could account for the basal release of catecholamines in normoxia unrelated to any effect on TASK activity.…”
Section: Relative Roles Of Task and Bk In Stimulus-secretion Couplingsupporting
confidence: 64%
“…Presence of spontaneous oscillation in [Ca 2+ ] i has also been reported earlier [28]. Because glomus cells in the carotid body are believed to be electrically-coupled by gap junctions [2], it is possible that spontaneous [Ca 2+ ] i oscillations occur under normoxic conditions for all glomus cells in vivo, but not in dispersed cells. Such [Ca 2+ ] i oscillations could account for the basal release of catecholamines in normoxia unrelated to any effect on TASK activity.…”
Section: Relative Roles Of Task and Bk In Stimulus-secretion Couplingsupporting
confidence: 64%
“…For efficient and acute hypoxia induction, 1 mM sodium dithionite (Na 2 S 2 O 4 , Sigma, 157953) was used to chemically consume the dissolved oxygen in the culture medium. [74][75][76] It is reported that Na 2 S 2 O 4 can lower pO 2 to 10 Torr compared with 30 Torr pO 2 induced by 100% N 2 . 77 After adding Na 2 S 2 O 4 , the pH of the DMEM/F-12 medium was adjusted to 7.4 and maintained by HEPES buffer considering the acidification potential of Na 2 S 2 O 4 .…”
Section: Methodsmentioning
confidence: 99%
“…Several authors have shown that, in hypoxic chambers, between 3 and 24 hours are required for the oxygen concentrations in the liquid phase to reach equilibrium with the gas mixture in the chamber (Allen et al, 2001; Mueller et al, 2009), making the clinically relevant rapid induction of hypoxic conditions impossible in these models. Hypoxic conditions can also be induced by the addition of cobalt chloride (Cheng et al, 2013; Garayoa et al, 2000; Gotoh et al, 2012) or sodium dithionite (Abudara et al, 2002; Mancarella et al, 2011; Yu et al, 2007), or by the application of the hypoxia-inducing enzymes glucose oxidase and catalase (Askoxylakis et al, 2011; Baumann et al, 2008; Mueller et al, 2009). Although the last-mentioned systems are easy to handle and rapidly induce hypoxic conditions, one of their major disadvantages is that the cells are in direct contact with the hypoxia-inducing agents.…”
Section: Discussionmentioning
confidence: 99%